CRAFTING SMART CITIES IN THE GULF REGION: A COMPARISON OF MASDAR AND LUSAIL - Tok, Evren; Al Mohammad, Fatemah; Al Merekhi, Maha (European Scientific Journal, ESJ, 2014)
Deployment of Information Communication Technologies (ICTs) in crafting smart cities in the Gulf Cooperation Council region including Saudi Arabia, Kuwait, United Arab Emirates, Qatar, Oman and Bahrain. Increasing economic dynamism in the GCC region has led development authorities, infrastructure companies, governmental and corporate entities to be more cognizant of deploying ICT solutions for various infrastructural platforms such as intelligent transportation, telecommunications, airports, sustainable environments, public safety, energy efficient buildings, residential and utilities projects. These projects not only stretch the limits of creativity, but also inform us about the neoliberal trajectories pursued by “globalizing” cities and their excessive focus on sustaining competitiveness. This study looks at these trajectories by specifically focusing on the interstices of smart cities and competitiveness through the role played by communication technologies. An initial question to tackle with pertains to the definition of a smart city as this concept is used in diverse ways in the literature. Transforming the cities into smart ones is a newly emerging strategy to deal with the problems created by the urban population growth and rapid urbanization. Smart city is often defined as “an icon of a sustainable and livable city.” Why Gulf countries have been investing in smart cities? Is the emergence of smart cities a mere reflection or neoliberal urbanization or are there other dynamics that we need to take into consideration? This paper attempts to convey the message that smart cities are crucial means of building social capital and also attaining better governance mechanisms in the Gulf.